2009
DOI: 10.5194/acp-9-3357-2009
|View full text |Cite
|
Sign up to set email alerts
|

Hydration increases the lifetime of HSO<sub>5</sub> and enhances its ability to act as a nucleation precursor – a computational study

Abstract: Abstract. Recent experimental findings indicate that HSO 5 radicals may play a key role in the nucleation of atmospheric SO 2 oxidation products. HSO 5 radicals are metastable intermediates formed in the SO 2 oxidation process, and their stability and lifetime are, at present, highly uncertain. Previous high-level computational studies have predicted rather low stabilities for HSO 5 with respect to dissociation into SO 3 +HO 2 , and have predicted the net reaction HSO 3 +OH→SO 3 +HO 2 to be slightly exothermal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 46 publications
4
24
0
Order By: Relevance
“…Its features have been reported and discussed recently by Solimannejad and co-workers 30 and our results, regarding the optimized geometries and energies, compare quite well with previous works in the literature. 30,63 It is only worth pointing out here that, as it has been shown by Solimannejad and co-workers, 30 the AIM analysis at the bcp of the SÁ Á ÁO(OH) interaction presents features of weak interaction character (the topological values are r = 0.0653, r 2 r = 0.1156, and H = À0.0100 a.u.). This complex has C s symmetry ( 2 A 0 0 electronic state) and the unpaired electron is mainly located on the OO group of the hydroperoxyl radical moiety, in a plane perpendicular to the SO 3 plane, so that it does not participate in the interaction between the HO 2 and SO 3 moieties.…”
Section: Technical Details Of the Calculationssupporting
confidence: 52%
“…Its features have been reported and discussed recently by Solimannejad and co-workers 30 and our results, regarding the optimized geometries and energies, compare quite well with previous works in the literature. 30,63 It is only worth pointing out here that, as it has been shown by Solimannejad and co-workers, 30 the AIM analysis at the bcp of the SÁ Á ÁO(OH) interaction presents features of weak interaction character (the topological values are r = 0.0653, r 2 r = 0.1156, and H = À0.0100 a.u.). This complex has C s symmetry ( 2 A 0 0 electronic state) and the unpaired electron is mainly located on the OO group of the hydroperoxyl radical moiety, in a plane perpendicular to the SO 3 plane, so that it does not participate in the interaction between the HO 2 and SO 3 moieties.…”
Section: Technical Details Of the Calculationssupporting
confidence: 52%
“…In order to distinguish between sunny and cloudy conditions, the cloud cover was estimated with the clear sky index (CSI) described by Marty and Philipona (2000). The CSI is defined as the ratio between the apparent emittance and the theoretical clear sky apparent emittance and is calculated from the atmospheric long-wave radiation, air temperature, and relative humidity.…”
Section: Determination Of Cloud Coveragementioning
confidence: 99%
“…Eisele, 1989b;Eisele et al, 2006), but to our knowledge the only previous atmospheric observations of the SO − 5 ion was by Junninen et al (2010). Model studies on the role of HSO 5 in the nucleation process has also been performed by Kurtén et al (2009), and this metastable radical has been found to be significantly stabilized by hydration, i.e. by forming clusters with water molecules, in ambient conditions.…”
Section: Negative Spectramentioning
confidence: 99%